The Alternative Selection for Internet of Things (IoT) Implementation in Medical Rehabilitation - Rayi Adila Paramita, Muhammad Dachyar (International Journal of Advanced Science and Technology, 2020)
Medical rehabilitation services face problems in terms of limited duration and intensityof therapy. The implementation of the Internet of Things (IoT) in medical rehabilitationhelps doctors and nurses to provide accurate care and faster recovery which couldimprove the service quality. This study aims to choose the best alternative IoT that can beimplemented in medical rehabilitation units in hospitals by taking into account the factorsof IoT implementation and hospital financial capability. The alternative options forimplementation of IoT: Motion Gaming Rehabilitation, Virtual reality-basedrehabilitation, Robot Therapy, Brain Computer Interfaces. The opinions of experts wereused to identify and select factors and sub-factors that support the process of applyingIoT in medical rehabilitation in hospitals. The Best Worst Method (BWM) method is usedto obtain priority weighting from the criteria and sub-criteria for applying IoT. TheAdditive Ratio Assessment (ARAS) method is used to obtain the utility level of eachalternative IoT. The Zero One Goal Programming method is used to decide whether theimplementation of IoT is chosen based on limitations such as the ARAS utility level ofeach alternative, procurement and installation costs, training costs, and maintenancecosts. The final result, virtual reality-based rehabilitation is chosen based on the factorsof IoT implementation and the hospital financial capability.